(3MSf GdeOO aj eYQaI af GdYOOs - (3HQgGf GdOjf CHh ESMGb EHQGgje Hf YeQ Hf EHQGgje Hf Ndjd GdLYHQj,J (B732 (3g` s ((3eMeO Hf CMeO Hf eMeO GdENejei s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd GdbQBf eaUdkG ShQkG hBjGJ s
(3BNQgG (B:s
(3GdhGh NeSI hYTQhf CdakG hNeSI hKeGfhf bGd eDdag aQZJ ef JCdjag ai djdI GdLeYI ai UaQ SfI SHY hSHYeGFI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B49 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B14s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3JLhjO hbQGAGJ (B21) s
Keywords: (3GdbQGAGJ hGdJLhjOs